STRUCTURAL DYNAMIC OF SEAGRASS COMMUNITIES IN THE PHU QUOC ISLAND (KIEN GIANG PROVINCE) - huong, Tu Thi Lan (Vietnam Journal of Marine Science and Technology, 2009)
Three seagrass species at eight sites in the Phu Quoc island (Kien Giang province) were surveyed using the quadrat sampling method in May 2006, September and December 2007. Density, biomass ofthree species and environmental factors were analyzed to determine dynamics and correlation using ANOVA - two factor. ANOVA showed that temperatures, turbidirty, rain fall influence seagrass density as well as biomass. Three seagrass species reached maximum shoot density and biomass in December (dry season) and decline in May (rainy season). Average total biomass ofseagrasses ranged from 210 DWg/m2 (Enhalus acoroides); 225.52 DWg/m2 (Cymodocea serrulata); 239.23 DWg/m2 (Thalassia hemprichii). Average shoot density ofEnhalus acoroides: 74 shoots/m2; Thalassia hemprichii: 520 shoots/m2; Cymodocea serrulata: 774 shoots/m2.